Establishing a reentry procedure for human immunodeficiency virus screening–reactive donors in China. Issue 1 (10th September 2015) - Li, Ling; Xu, Ting; Yang, Tao; Zang, Liang; Cheng, Weifang; Lin, Hongkeng; Zhu, Shaowen; Zhao, Binghai; Duan, Rong; Li, Chunling; Huang, Mei; Liu, Yuqiang; et al.
Abstract : BACKGROUND: Screening of blood donors for antibody to human immunodeficiency virus Types 1 and 2 (anti‐HIV‐1/2) and/or HIV nucleic acid test (NAT) is a well‐established venue to prevent HIV transfusion‐transmitted disease. However, with the current available technologies, HIV testing may result in donor loss due to false‐positive results. This study intended to establish a donor reentry procedure for HIV screening–reactive donors in China. STUDY DESIGN AND METHODS: From September 1, 2013, to August 31, 2014, a total of 465 donors from 14 Chinese blood centers were enrolled in this study. Enrollment criteria include all donors who were screened reactive or belonged to the "gray zone" by enzyme‐linked immunosorbent assay and/or reactive by NAT when tested at the local blood centers. All donor samples were sent to a central HIV confirmation laboratory where anti‐HIV‐1/2 and HIV individual‐donation NATs were conducted. If the results were reactive for anti‐HIV‐1/2, then the samples were tested with a recombinant immunoblot assay. RESULTS: Based on the repeat testing at the central HIV confirmation laboratory 8 or 16 weeks after the study, 252 donors of 465 (54.2%) who completed the study could be classified in two categories for HIV status: 45 (18%) true positive and 207 (82%) false positive. A total of 213 of 465 (45.8%) donors were lost on follow‐up and, thus, their HIV status cannot be determined with certainty. Based on these data, a donor reentry procedure was proposed. CONCLUSION: Based on our proposed donor reentry procedure for HIV screening–reactive donors, a majority of screening‐positive donors (82%, 207/252) can be reentered safely.